2019
DOI: 10.1159/000497162
|View full text |Cite
|
Sign up to set email alerts
|

Renal Consequences of Therapeutic Interventions in Premature Neonates

Abstract: An infant is described as “preterm” if they are born before 37 weeks of gestation. As nephrogenesis does not complete until 36 weeks of gestation, premature infants are often born with underdeveloped kidneys. Current evidence strongly suggests that this leaves those born prematurely more susceptible to developing kidney-related conditions later in life. Although the incidence of premature birth steadily increases each year in the United Kingdom, reports of perinatal death following preterm labour are falling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…The data (Figure S1A-C) showed that there was no difference in body weight and kidney weight between the experiment and control group. Studies in rodents, sheep, and non-human primates suggested that corticosteroids might harm the kidneys by significantly reducing the number of nephrons [28] . To investigate the effects of excessive GCs treatment on the kidneys, we performed kidney histological studies to detect the potential alterations in kidney morphology.…”
Section: Dex Treatment Affected the Expression Of Genes Involved In Metabolism Inflammation And Immune Responsementioning
confidence: 99%
“…The data (Figure S1A-C) showed that there was no difference in body weight and kidney weight between the experiment and control group. Studies in rodents, sheep, and non-human primates suggested that corticosteroids might harm the kidneys by significantly reducing the number of nephrons [28] . To investigate the effects of excessive GCs treatment on the kidneys, we performed kidney histological studies to detect the potential alterations in kidney morphology.…”
Section: Dex Treatment Affected the Expression Of Genes Involved In Metabolism Inflammation And Immune Responsementioning
confidence: 99%
“…An ambiguous role is played by drugs administered to preterm and low birth weight babies. The therapeutic benefit of drugs is balanced against the frequently unknown nephrotoxic potential [12][13][14][15].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Indeed, Gjerde et al found a relation between preterm birth and ESRD in males but not in females; this gender difference was not revealed in the LBW or SGA group [ 8 ]. Potentially, preterm infants might have enough renal reserve, but postnatal (nephrotoxic) medication during their admission at the neonatal intensive care unit is what might put them at risk [ 10 ].…”
Section: Different Underlying Mechanismsmentioning
confidence: 99%